Critical Success Factors for Implementing Off-Site Modular Construction projects in UAE: A Fuzzy DEMATEL Approach - EL KHATIB, AHMAD TAHA (2022)
Offsite Modular Construction, have started gaining popularity in the middle east in the last few years as it is seen to improve quality, reduce construction time and reduce safety related accidents. This research studied and found the influence and relationship between different critical success factors related to the implementation of offsite construction. the research first identified Critical Success Factors (CSFs) from literature review, then grouping the factors into Principal Success Factors (PSFs) using the affinity diagram method through consulting offsite modular construction experts. A survey found the ranking of the critical success factor and the DEMATEL (Decision Making Trial and Evaluation Laboratory), which is Multi-Criteria Decision Making (MCDM) method, was used with fuzzy set theory methods for finding the causes, effects and influences between the different PSFs to assist executives in taking strategic high level decisions. Fuzzy-DEMATEL was also used for finding the causes, effects and influences between the CSFs which would help project managers and professionals in taking project level decision. After analyzing the data to find the causes, effects and relationships between the different factors, the results of the study found that 5 PSFs and 15 CSFs were causes while 2 PSFs and 10 CSFs were effects. This approach can be considered for future and more extensive research on this subject.